Optical power control to efficiently handle flex-grid spectrum gain over existing fixed-grid network infrastructures - Kanj, M.; Le Rouzic, E.; Amar, D.; Auge, J. L.; Cousin, B.; Brochier, N. (ICNC : 2016 International Conference on Computing, Networking and Communications : 15-18 February 2016, 2016)
The exponential traffic growth in optical networks has triggered the evolution from Fixed-Grid to Flex-Grid technology. This evolution allows better spectral efficiency and spectrum usage over current networks in order to facilitate dynamic and huge traffic demands. The integration of Flex-Grid technology increases the number of optical channels established over optical links, leading, however, to an increase in amplification power and possibly saturating optical amplifiers. In this work, we propose a power adaptation process that takes advantage of link optical signal to noise ratio (OSNR) margins to allow network operators to support this power increase while maintaining the use of legacy amplifiers. Results show that controlling channel optical power benefits from the Flex-Grid in terms of spectrum and capacity gain using in-place amplifier infrastructure.